Refleksi Kritis Pancasila dalam Idealitas dan Realitas Pendidikan di Madrasah Ibtidaiyah - Ahmad Shofiyuddin Ichsan; Taqwa Nur Ibad; Agus Riyan Oktori (Bidayatuna, 2023)
This research aims to reveal in detail how Pancasila is used as the basis of Indonesian philosophy. Researchers studied two main studies, namely Pancasila which is understood in the context of ideals and realities of life, especially in basic education (Madrasah Ibtidaiyah). This research method uses a qualitative descriptive method with a type of library research using a pragmatic approach. Research data is taken from scientific work related to research. The analysis technique in this research uses content analysis. The results of the research show that there is a Project Movement for Strengthening the Pancasila Student Profile / Project for Strengthening Pancasila Students (P5) and the Rahmatan Lil 'Alamin Student Profile which is a unified spirit that mutually strengthens each other. Both adhere to the Pancasila philosophy and uphold diversity and human values. However, these ideals are not commensurate with the existing reality, so that the Pancasila philosophy in basic education has several challenges, including liberalism, individualism, pragmatism, hedonism and external religious ideologies.